2016
DOI: 10.4268/cjcmm20161413
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS combined with AMDIS and Koáts retention index to investigate dynamic change rules of volatile components from Atractylodis Macrocephalae Rhizoma with different stir-baking degrees

Abstract: To investigate the dynamic change rules of volatile components from Atractylodis Macrocephalae Rhizoma with different stir-baking degrees (from slight stir-baking, stir-baking to yellow, stir-baking to brown, to stir-baking to scorch). In the present experiment, the Atractylodis Macrocephalae Rhizoma samples with different stir-baking degrees were collected at different processing time points. The contents of volatile oil in various samples were determined by steam distillation method, and the volatile compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the PCMM, heat refers to the size and duration of fire when the drug is heated, which is a key factor affecting the quality of decoction pieces. Studies have shown that with the change of fire degree, the content of volatile components, amino acids and reduced sugars in drugs have changed significantly ( Chen et al, 2016 ; Hu et al, 2016 ). Therefore, through the digital technology, the various influencing factors in the processing are objectively quantified, and then the artificial intelligence technology is used to adjust and control the fire, time, temperature and processing end point, which is conducive to the standardization of processing technology and the quality of decoction pieces.…”
Section: Applications Of Digital and Intelligent Technologies In Proc...mentioning
confidence: 99%
“…In the PCMM, heat refers to the size and duration of fire when the drug is heated, which is a key factor affecting the quality of decoction pieces. Studies have shown that with the change of fire degree, the content of volatile components, amino acids and reduced sugars in drugs have changed significantly ( Chen et al, 2016 ; Hu et al, 2016 ). Therefore, through the digital technology, the various influencing factors in the processing are objectively quantified, and then the artificial intelligence technology is used to adjust and control the fire, time, temperature and processing end point, which is conducive to the standardization of processing technology and the quality of decoction pieces.…”
Section: Applications Of Digital and Intelligent Technologies In Proc...mentioning
confidence: 99%